If Music is Ongoing Experience, What Might Music Theory Be? . A Suggestion from the Drastic - Christopher F. Hasty (Zeitschrift der Gesellschaft für Musiktheorie)
The current opening of musicology to questions of performance and embodied meaning calls for a theorizing of musical experience that would not remain stuck in oppositions of subject and object, mind and body, process and product. If we take experience as essentially predetermined by the musical work or, in cognitivist information processing terms, by rule-governed mechanisms for manipulating internal representations (be these rules syntactic or semantic) we shall not be able to account for the creativity of music and the production of novel meaning. The complexity or messiness of such production may seem an impediment to understanding music – it would seem to lead to the vagaries of the merely subjective, to mere appearance, or to a hopeless relativism that would in the end leave us speechless. In this essay I will take the creativity of experiencing and all the complexity that comes with it as a positive fact that might lure us to think about time and process in music. Such a thinking could open many avenues for connecting theory and practice and for connecting music theory with other disciplines of musical scholarship.